OS DIREITOS HUMANOS E A LUTA PELA TERRA: a experiência da Turma Evandro Lins e Silva - Maria Inez Pereira Pinheiro (Revista de Políticas Públicas, 2018)
The text discusses how the struggle for human rights strategically composes the struggle for land made by the MST, articulated to other social organizations. Reflects on collective rights as an overcoming of the restrictive dimension of individual rights, indicating that the judiciary presents difficulties for its recognition. It brings the experience of the constitution of the first course of Law in Brazil, focused exclusively to meet the demands of social movements, contextualizing the process, starting with conservative and reactionary actions in an attempt to prevent their realization. It concludes the revolutionary importance of this political initiative of the movements for the organization of the working class, in particular for the peasants organized by the MST.